Cockle Cleaning Machine - Siti Mariam; Suleiman, Amin Suffian; Mohd Afandi, Nurul Auni Afrina; Amin, Siti Zakiah; Hashim, Hairul Mubarak; Ngadimon, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2020)
Cockles are one of the popular protein choices that are often used in the preparation of dishes in Malaysia. However, since the cockles naturally live buried in mud and sediment, the cleaning process of the dirt from its shell can be quite tricky. In this study, the small size of the cockle cleaning machine with a capacity of 2 kg was designed for home and small business use purposes. This manual machine consists of main components, including water container, perforated drum, cleaning brush, shaft, and hand lever. The dirty cockles should be inserted into the drum through the open end section before it covered by the end cap. When the hand lever attached to the drum is rotated clockwise, the cleaning brush on the shaft will be rotated together and will rub and remove dirt on the cockles’ shell surface. The water that is put in the cleaning container up to a specific water level will then help the cleaning process of removing this dirt. With the conceptual design that can be offered by this cockles cleaning machine, hopefully, it will benefit homemakers, restaurants, and related businesses in the future.